2011
DOI: 10.1021/jm201168g
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel and Potent Class of F. tularensis Enoyl-Reductase (FabI) Inhibitors by Molecular Shape and Electrostatic Matching

Abstract: Enoyl-acyl carrier protein (ACP) reductase, FabI, is a key enzyme in the bacterial fatty acid biosynthesis pathway (FAS II). FabI is an NADH-dependent oxidoreductase that acts to reduce enoyl-ACP substrates in a final step of the pathway. The absence of this enzyme in humans makes it an attractive target for the development of new antibacterial agents. FabI is known to be unresponsive to structure-based design efforts due to a high degree of induced fit and a mobile flexible loop encompassing the active site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 54 publications
3
76
0
Order By: Relevance
“…Recently, our laboratory reported the identification and structural characterization of a novel series of benzimidazole FabI inhibitors as a new chemical scaffold with promising enzyme and antibacterial activity. 14, 15 We now report the structural and biological evaluation of several second generation benzimidazole compounds with low nanomolar enzyme inhibition and promising antibacterial activity, not only against F. tularensis , but also against the more prevalent pathogen, S. aureus and MRSA. Our co-crystal structures demonstrate the binding modes of these second generation inhibitors in FtFabI and lay a solid foundation for analyzing strategies to improve pharmacokinetic properties while maintaining FabI inhibition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our laboratory reported the identification and structural characterization of a novel series of benzimidazole FabI inhibitors as a new chemical scaffold with promising enzyme and antibacterial activity. 14, 15 We now report the structural and biological evaluation of several second generation benzimidazole compounds with low nanomolar enzyme inhibition and promising antibacterial activity, not only against F. tularensis , but also against the more prevalent pathogen, S. aureus and MRSA. Our co-crystal structures demonstrate the binding modes of these second generation inhibitors in FtFabI and lay a solid foundation for analyzing strategies to improve pharmacokinetic properties while maintaining FabI inhibition.…”
mentioning
confidence: 99%
“…In our prior studies reporting hit identification, structural and enzymatic analyses of the first-generation benzimidazole FabI inhibitors, 14, 15 the initial SAR was constructed primarily by testing commercially available benzimidazole analogs, resulting in a limited understanding of the structure-activity relationship. We now report activities from synthetic analogs of our prior best hit, compound 1 (Figure 1), and find that the second generation compounds display enhanced enzymatic inhibitory activity, along with significantly improved antibacterial activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structure and ligand-based virtual screening approaches have been used previously to design inhibitors for important targets, such as FabI and M. tuberculosis malate synthase (46,47). It has been shown that virtual screening involving the fusion of structure-and ligand-based methods is an effective tool to achieve a higher hit rate and provide wider structural coverage of chemical space (30), and a combination of these methodologies was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…30 MBC values were estimated using the standard method of testing all negative MIC wells (no visible growth) for evidence of viable bacteria by transferring an aliquot of MIC dilution culture media to antibiotic-free agar plates. Medium (100 lL) from each negative (clear) well in MIC assays was streaked onto LB agar plates, and the plates were incubated for 72 h for detection of bacterial growth.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bactericimentioning
confidence: 99%